Hubungan Antara Pengetahuan Guru Tentang Undang-Undang Nomor 35 Tahun 2014 Dengan Sikap Guru Kepada Peserta Didik: Studi Korelasi Pada Guru SMP Negeri Kecamatan Mendo Barat - Muhammad Ghozali; Dinar Pratama (Sustainable, 2020)
This study aims to determine whether there is a relationship between teacher knowledge about Law Number 35 of 2014 and the attitude of teachers to students. This research is a type of quantitative research with a correlational method. Through data collection techniques in the form of tests and questionnaires. The population taken was all teachers at SMP Negeri Mendo Barat sub-district totaling 68 people with a saturated sample of 68 people. Then the technical data analysis used to test the hypothesis is the product-moment correlation with the teacher's knowledge variable about Law Number 35 of 2014 (X) with the Attitude of Teachers to Students (Y). Furthermore, to test the validity of the independent variable instrument items using the Biserial Point Correlation the results are 29 valid and 1 drop, while the validity of the dependent variable shows 33 valid and 15 drops with a coefficient of 0.20. Then the reliability for the teacher knowledge variable uses the Kuder Richardson-20 (KR-20) and the teacher's attitude variable to students is the Cronbach Alpha formula with an efficiency of 0.71. The results of this study indicate that the teacher's knowledge of Law Number 35 of 2014 with the attitude of the teacher to students with a coefficient of 0.261.